Perancangan Jaringan Wifi di Desa Landungsari Guna Efisiensi Tagihan Bulanan - Mohammad Andy Sampurno; Poerbaningtyas E (J-INTECH ( Journal of Information and Technology), 2022)
This study builds the RtRw Net wifi network to meet the internet access needs of the community in the Rt.04 Rw.07 area of ​​Landungsari Village with affordable usage costs. At this time, the community in the area of ​​Rt.04 Rw.07 Landungsari Village has a high need for internet access and to meet the internet access needs of the people in the region, they purchase internet quotas which in a month can make three to four purchases of internet quotas and internet quotas. purchased has an internet quota usage limit. Therefore, many people spend a lot of money to buy internet quota in order to fulfill their internet access needs. In the construction of this wifi network, researchers have collected some information by conducting observations and interviews with people in the area. This wifi network was built using a proxy router as a voucher-based RtRw Net wifi network management and researchers created a website application using the Code Igniter framework using PHP and MySQL programming discussions for data storage in the database. The main stages in building a wifi network and website application include analysis of hardware requirements, software, network design, application design, proxy configuration, coding, testing and implementation of the network that was built and the application that has been made. that has been made can operate properly.